DETAILED STUDY OF THE VELOCITY SECTION BY INTEGRATING SEISMIC DATA OF SINGLE AND MULTIPLE PROFILING - Ahmadov, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The velocities of propagation of seismic waves are one of the most important kinematic parameters; the geological efficiency of seismic exploration ultimately depends on the accuracy and completeness of information about the velocities. Methods for determining effective velocities from seismic data, proposed for the period of application of seismic exploration by the method of reflected waves, are listed. The methods for determining the velocities are divided into 2 large groups: the first group includes methods for determining the effective velocities based on automatic or visual tracking of the in-phase axes (i.e. hodographs) of reflected waves on the seismograms of the OTP (common point of explosion) or CDP (common depth point), and then their approximation by hyperbolas, and the second group includes methods based on the use of seismic wave field analysis in controlled directions. The main disadvantages of the existing methods are indicated, the industrial method, which is widely used at the present time, is highlighted, based on the analysis of the wave field in controlled directions, which do not provide sufficiently accurate and complete information for solving the traditional problem of kinematic interpretation, i.e. transition from time sections to migrated deep ones. A new method for determining the effective velocity is proposed, which is fundamentally different from the methods used so far in the practice of seismic exploration, since in this method, seismic data of single and multiple profiling are used not separately, as it was until now, but in a complex manner. Formulas are derived for determining the effective speed from the data of single and multiple profiling. A method for determining the effective speed has been developed and a sequence of procedures for solving the problem is presented. The results of research on a specific example are given by solving the direct and inverse problems for the Sazhdag area of the Mesopotamia of the Kura and Iori rivers. The influence of errors in the values of the parameters included in the formula for calculating the effective speed on the final results is investigated. At the end of the article, the main advantages of the proposed method are listed.
Keywords: 2D and 3D seismic; effective velocity; stacking rate; time gradient; time sections